Genetic Contribution to Concern for Nature and Proenvironmental Behavior. (20th October 2021) - Chang, Chia-chen; Nghiem, Thi Phuong Le; Fan, Qiao; Tan, Claudia L Y; Oh, Rachel Rui Ying; Lin, Brenda B; Shanahan, Danielle F; Fuller, Richard A; Gaston, Kevin J; Carrasco, L Roman
Abstract: Earth is undergoing a devastating extinction crisis caused by human impacts on nature, but only a fraction of society is strongly concerned and acting on the crisis. Understanding what determines people's concern for nature, environmental movement activism, and personal conservation behavior is fundamental if sustainability is to be achieved. Despite its potential importance, the study of the genetic contribution to concern for nature and proenvironmental behaviors has been neglected. Using a twin data set (N = 2312), we show moderate heritability (30%–40%) for concern for nature, environmental movement activism, and personal conservation behavior and high genetic correlations between them (.6–.7), suggesting a partially shared genetic basis. Our results shed light on the individual variation in sustainable behaviors, highlighting the importance of understanding both the environmental and genetic components in the pursuit of sustainability.